2022
DOI: 10.3389/fpsyg.2022.906300
|View full text |Cite
|
Sign up to set email alerts
|

Sport Participation and Psychosocial Factors Which Influence Athletic Identity in Youth Athletes With Anterior Cruciate Ligament Injury

Abstract: Athletic identity, or the degree with which individuals identify with the athlete role, is an important rehabilitation factor for sports care providers to consider; however, it lacks extensive study in youth. The purpose of this study was to identify demographic, sport participation, and psychosocial measures which correlate with youth athletic identity after anterior cruciate ligament injury. Participants completed standardized sports medicine intake and patient-reported outcome measures, including the Athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
(56 reference statements)
3
7
0
Order By: Relevance
“…Similar studies in mixed cohorts of youth and young adults reported AIMS scores between 44.2 and 57.5, which further support the current data ( Manuel et al, 2002 ; Brewer et al, 2003 ; McKay et al, 2013 ; Padaki et al, 2018 ; McGinley et al, 2022 ). The observed decrease in AIMS confirms Brewer and Cornelius’ (2010) findings in adults who reported a gradual decline in athletic identity over 24 months post-ACLR, with the most substantial decline at 6–12 months post-ACLR.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar studies in mixed cohorts of youth and young adults reported AIMS scores between 44.2 and 57.5, which further support the current data ( Manuel et al, 2002 ; Brewer et al, 2003 ; McKay et al, 2013 ; Padaki et al, 2018 ; McGinley et al, 2022 ). The observed decrease in AIMS confirms Brewer and Cornelius’ (2010) findings in adults who reported a gradual decline in athletic identity over 24 months post-ACLR, with the most substantial decline at 6–12 months post-ACLR.…”
Section: Discussionsupporting
confidence: 90%
“…In this cohort, only pre-ACLR AIMS scores were different between males and females. Certain studies report that sex and athletic identity are related ( Babić et al, 2015 ; Şekeroğlu, 2017 ; McGinley et al, 2022 ) though the pattern is inconsistent. Others show no such relationships ( Proios et al, 2012 ; Piatt et al, 2018 ; Costa et al, 2020 ; Rae and Jenkins, 2021 ), yet only McGinley et al and Piatt et al studied youth exclusively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations